ANALISIS KINERJA PEGAWAI BERDASARKAN TUGAS POKOK DAN FUNGIS PADA KANTOR KECAMATAN SARUDU KABUPATEN MAMUJU UTARA - Haris, Abdul (Katalogis, 2018)
This study aimed to analyze employee performance based on duties and functions and to analyze factors inhibiting employee performance based on duties and functions, at sarudu District Office North Mamuju Regency. The concept used in this study to examine determinants of employee performance based on duties and functions was Handokoâ€™s Theory, comprising efficiency and effectiveness.This study used purposive sampling with specified informants as much as 5 people and key informant was head of Sarudu District, Mamuju Utara Regency. The data collection technique was observation, interview, and documentation. The results showed that employee performance based on dutes and functions at sarudu District office North Mamuju Regency had not been good seen ftrom the Efficiency aspect comprising understanding and mastering tasks, for the employees did not fully understand and master; and seen from the Effectiveness aspect, for the performance of services given had not been maximal evidenced by the presence of complaints form the public due to the unfamiliarty of the people and the bureaucracy faced by the employees. While, the factors inhibiting employee performance due to duties and functions were cultures reflected in the behavior of the employees; the internal side of the employee measured from work ethic, motivation, discipline, and dependence of the employees to the leaders who was still very high, both in terms of discipline and work; as well as the external side of the employees, that the interaction pattern in providing services had not been professional.Â